Semiprime Fuzzy Modules - Hamil, M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper we introduce the notion of semiprime fuzzy module as a generalization of semiprime module. We investigate several characterizations and properties of this concept.